2020
DOI: 10.1029/2020gl088388
|View full text |Cite
|
Sign up to set email alerts
|

A 25‐Year History of Volcano Magma Supply in the East Central Aleutian Arc, Alaska

Abstract: Using ~25 years of GPS and InSAR observations and the time‐dependent inversion filter, we invert for the volume change history of three active volcanoes in the east central Alaska Aleutian arc and the secular velocity of the region. The inferred time‐dependent volume change shows (1) two exponentially decaying pulses followed by a nearly linear inflation period at Westdahl volcano, (2) multiple episodic inflation events at Akutan volcano, and (3) transient volcanic inflation and long‐term deflation signals at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Nevertheless, we have some differences in the ratio between the semimajor and semiminor axes and the dipping angle for the spheroidal source. These discrepancies can be attributed to the remaining uncertainties in the campaign sites and atmospheric noises that remains after the SBAS processing, and also the different time intervals covered by the data sets—in essence we assume a constant process, while we know that the deformation rates are time varying (Figure 2a, Xue & Freymueller, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we have some differences in the ratio between the semimajor and semiminor axes and the dipping angle for the spheroidal source. These discrepancies can be attributed to the remaining uncertainties in the campaign sites and atmospheric noises that remains after the SBAS processing, and also the different time intervals covered by the data sets—in essence we assume a constant process, while we know that the deformation rates are time varying (Figure 2a, Xue & Freymueller, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For Fisher Caldera, they suggested a contraction of magma as a consequence of crystallization and degassing or depressurization of the hydrothermal system. Xue and Freymueller (2020) analyzed the GNSS measurements after the 1992 eruption until 2019 and used previous InSAR results from Lu et al (2003) and Gong et al (2015) to support the hypothesis that the arrival of discrete pulses of new magma explains the stair-stepping behavior in time of the magma pressure.…”
Section: Case Study: Westdahl Volcano and Fisher Calderamentioning
confidence: 99%
“…Similar to other locations with observations far from the deformation front, geodetic data in the Fox Islands section can be fit by multiple models, including those that place complete or nearly complete locking over a narrow patch close to the trench (Xue & Freymueller, 2020) or lower values of coupling on a deeper patch . Because Nicolsky et al (2016) found the best model fit to the 1957 tsunami required predominantly shallow slip on the interface, we draw primarily from Xue and Freymueller (2020) and model 93% coupling extending ˜40 km arcward from the deformation front, corresponding to a depth of ˜15 km along the subduction interface (Figure 5).…”
Section: Fox Islands Sectionmentioning
confidence: 91%
“…Two major inflation patterns are identified ‐ continuous inflation events produced from spatially steady sources at time‐varying rates at Okmok, Akutan and Westdahl, and episodic inflation events that occur intermittently at Great Sitkin, Seguam, and Makushin. The persistent inflation events are the continuation of successive inflation periods that started prior to 2015, with similar source locations and depths (Lu et al., 2010; Wang et al., 2018, 2021; Xue & Freymueller, 2020). The inflating episodes detected at Seguam and Makushin are analogous to the ones in previous deformation surveys and are very likely produced from the same sources (Lee et al., 2013; Xue & Freymueller, 2020).…”
Section: Temporal and Spatial Characteristics Of The Along‐arc Volcanismmentioning
confidence: 96%
“…The persistent inflation events are the continuation of successive inflation periods that started prior to 2015, with similar source locations and depths Wang et al, 2018Wang et al, , 2021Xue & Freymueller, 2020). The inflating episodes detected at Seguam and Makushin are analogous to the ones in previous deformation surveys and are very likely produced from the same sources (Lee et al, 2013;Xue & Freymueller, 2020). The persistent inflation observations likely indicate continued magma supply to the existing magmatic reservoirs and are usually associated with more persistent temporal patterns while the episodic inflation episodes show more intermittent features and are typically suggestive of magma accumulations in stages.…”
Section: Temporal and Spatial Characteristics Of The Along-arc Volcanismmentioning
confidence: 96%